2017
DOI: 10.12968/jowc.2017.26.12.784
|View full text |Cite
|
Sign up to set email alerts
|

Management of chronic diabetic foot ulcers using platelet-rich plasma

Abstract: This study will provide more evidence for the use of autologous PRP for DFUs in patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 11 publications
0
49
0
3
Order By: Relevance
“…It is acknowledged that the role of platelets at the wound site can be twofold: platelets form an aggregate at the wound site and trigger the inflammatory phase of wound healing,31 but platelets may also be key in the later stages of wound healing by modulating PBMC release of cytokines and growth factors 21. The use of PRP has been successful in a number of clinical settings, particularly in chronic conditions that are characterised by persistently dysregulated inflammation 32, 33. We can hypothesise that a mechanism to promote good healing with PRP may be the ability of platelets to interact with resident leucocytes and dampen down their inflammatory responses at the wound site.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is acknowledged that the role of platelets at the wound site can be twofold: platelets form an aggregate at the wound site and trigger the inflammatory phase of wound healing,31 but platelets may also be key in the later stages of wound healing by modulating PBMC release of cytokines and growth factors 21. The use of PRP has been successful in a number of clinical settings, particularly in chronic conditions that are characterised by persistently dysregulated inflammation 32, 33. We can hypothesise that a mechanism to promote good healing with PRP may be the ability of platelets to interact with resident leucocytes and dampen down their inflammatory responses at the wound site.…”
Section: Discussionmentioning
confidence: 99%
“…21 The use of PRP has been successful in a number of clinical settings, particularly in chronic conditions that are characterised by persistently dysregulated inflammation. 32,33 We can hypothesise that a mechanism to promote good healing with PRP may be the ability of platelets to interact with resident leucocytes and dampen down their inflammatory responses at the wound site. Nami et al 21 similarly conclude that platelets participate in many, including late, stages of wound healing and this is a previously unappreciated role for this cell type.…”
Section: Discussionmentioning
confidence: 99%
“…Lesions may lead to lower limb infection, ulcer formation and the destruction of deep tissue (2). Diabetic foot wounds are prone to relapse and wound healing is extremely slow; as such, clinical treatments typically have poor outcomes, which may cause long-term physical and mental suffering and financial hardship for the patient (3).…”
Section: Introductionmentioning
confidence: 99%
“…A study on the treatment of neuropathic DFUs was conducted in Iran, using the PRP Secollow Kit SK50-20. This study observed a decrease in the ulcers in all groups after seven weeks, with total healing observed after eight weeks, and, upon monitoring the patients afterward, no recurrence was observed [86]. Another report mentioned a clinical case of a 71-year-old type II diabetes patient who suffered severe injuries in his feet due to his inability to feel high temperatures.…”
Section: Platelet-rich Plasma (Prp)mentioning
confidence: 55%